The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1751-7133.2009.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated With Nesiritide Administration for Acute Decompensated Heart Failure in the Emergency Department Observation Unit: A Single Center Experience

Abstract: The authors' purpose was to determine 30- and 180-day readmission and mortality rates for acutely decompensated heart failure patients receiving nesiritide in the emergency department observation unit. The authors conducted a retrospective evaluation of all patients admitted to the emergency department observation unit, stratified by nesiritide administration, from January 2002 to January 2004. Eligible patients had a primary diagnosis of acutely decompensated heart failure. Observation unit treatment was by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Three trials contributed to the analysis on total mortality with a comparison between nesiritide and placebo ( figure 3 ). 16 21 23 30–35 Compared with placebo, nesiritide indicated no increasing risk of total mortality, with an RR of 1.04 (95% CI 0.79 to 1.38; p=0.76; figure 3 ). As shown in figure 4 , there was no significant difference between the nesiritide and dobutamine group, regarding total mortality (RR 0.69; 95% CI 0.46 to 1.05; I 2 =0%; p=0.09).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three trials contributed to the analysis on total mortality with a comparison between nesiritide and placebo ( figure 3 ). 16 21 23 30–35 Compared with placebo, nesiritide indicated no increasing risk of total mortality, with an RR of 1.04 (95% CI 0.79 to 1.38; p=0.76; figure 3 ). As shown in figure 4 , there was no significant difference between the nesiritide and dobutamine group, regarding total mortality (RR 0.69; 95% CI 0.46 to 1.05; I 2 =0%; p=0.09).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen trials were double blind, 11 16 19 22 23 25 27–29 35 36 seven were open-label trials 8 12 20 26 31 32 34 and the remaining had concealed allocation. 21 24 30 33 The dose of nesiritide varied between 0 and 2 µg/kg (as an intravenous bolus) or between 0.005 and 0.03 µg/kg/min (as a continuous infusion). Follow-up durations were ≤30 days in 14 trials, 8 12 16 19–21 23 24 26 27 31 36 37 3 months in 3 trials 32 34 35 and 6 months in 6 trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nesiritide in patients with AHF is also associated with reductions in endogenously produced BNP, a laboratory value used clinically as a surrogate for cardiovascular congestion [24, 25]. Several small studies have shown a benefit of adding nesiritide to standard therapy on patient-reported relief of dyspnea [20, 26], but additional studies provided little support for nesiritide in reducing the frequency of rehospitalization [27-34] or mortality [26-28] in patients with AHF (Table 1). The previously mentioned VMAC study included 204 patients who received IV nesiritide [16] and demonstrated a statistically significant improvement in dyspnea at three hours post infusion in patients treated with nesiritide over those treated with NTG or placebo – leading to FDA approval of nesiritide for use in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies which enrolled patients within 24 hours of ED presentation provide evidence of blood pressure and dyspnea improvement, but lack conclusive evidence regarding their impact on long term outcomes such as hospital readmission and mortality rates. Studies which enrolled patients in the ED, or in an ED associated observation unit,[27, 30, 31] showed neutrality or only modest benefits of adding IV vasodilators in comparison to standard care alone. None of the large, multicenter investigations of IV vasodilators, such as ASCEND-HF or RELAX-AHF, specifically mandated ED enrollment, though some were conducted across numerous sites internationally and did enroll ED patients.…”
Section: Discussionmentioning
confidence: 99%